2018
DOI: 10.1111/cla.12343
|View full text |Cite
|
Sign up to set email alerts
|

Areas of endemism: to overlap or not to overlap, that is the question

Abstract: The concept of "areas of endemism", and the assumption that these patterns are always a consequence of vicariant events, are reviewed. This assumption is related to the idea that areas of endemism have well-defined limits and never share any surface with other areas of endemism because they must represent sister areas supported by sister taxa. Based on this idea, overlapping areas have been considered rarely, or ignored completely. Using a data set of mammals of North America, we test here whether the overlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…From the theoretical perspective that privileges vicariance and allopatric speciation (Harold & Mooi, 1994;Morrone, 1994), areas of endemism must not overlap and must be formed by groups of sister taxa. In agreement with other studies that tested this assumption and showed that overlapping patterns of endemism are common (Szumik, Pereyra, & Casagranda, 2018), we showed here that the areas of endemism of Bignonieae overlap substantially with many nested patterns (Figs. 4 and 6).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…From the theoretical perspective that privileges vicariance and allopatric speciation (Harold & Mooi, 1994;Morrone, 1994), areas of endemism must not overlap and must be formed by groups of sister taxa. In agreement with other studies that tested this assumption and showed that overlapping patterns of endemism are common (Szumik, Pereyra, & Casagranda, 2018), we showed here that the areas of endemism of Bignonieae overlap substantially with many nested patterns (Figs. 4 and 6).…”
Section: Discussionsupporting
confidence: 93%
“…Geographical pattern: Spatial con7guration of the consensus areas, which can be: a. Perfectly nested: One of the consensus area is completely included in the other; b. Nested with edge effect: Smaller consensus areas is completely included in another bigger area but one of its lines of cells lays outside and adjacent: c. Overlapping: Consensus areas overlap by at least two lines of cells but conserved also at least two lines of cells outside of their intersection zone (following terminology of Szumik et al, 2018). Ambiguous species: List of species shared by the group of consensus areas.…”
Section: Areas Of Endemism Of Tribe Bignonieae (Bignoniaceae)mentioning
confidence: 99%
“…The spatial component of endemism determined in our analysis was shaped by different processes, including historical, evolutionary, ancient and/or ecological factors, in addition to climatic shifts and sampling bias (Szumik et al, 2002; Morrone, 2009; Lu et al, 2018; Szumik et al, 2019). Shared events by endemic species may alter the spatial boundaries of an AE without changing its core sectors over time (see Gámez et al, 2014), such that these areas are detectable as historical biotic units.…”
Section: Discussionmentioning
confidence: 94%
“…Two major observations consistently emerged from all the analyses: a dramatic east/west split and a significant overlap or nestedness among the adjacent AEs within each of the two disjunctive groups -the two super-areas. Szumik et al, (2018) using a dataset of mammals of North America demonstrate that AEs consistently overlap and are rarely characterized by sister taxa. Many genera (e.g.…”
Section: Discussionmentioning
confidence: 99%